Academic Anxiety, Study Habit and Burnout as Predictors of Self-Esteem among University Student in Katsina State, Nigeria - SAYYADI, Sagir Ibrahim; SALISU, Abba Yangaiya (Ilorin Journal of Education, 2025)
The study investigated the relationship between academic anxiety, study habits, burnout, and self-esteem among university students in Katsina State, Nigeria. A correlational design study with a sample of 385 university students selected using a proportionate sampling technique. The study utilized standardized instruments, including the Academic Anxiety Scale, Study Habits Inventory, Maslach Burnout Inventory-Student Survey (MBI-SS), and Rosenberg Self-Esteem Scale (RSES). Multiple regression analysis revealed that academic anxiety (β = -.248, p < .001), study habits (β = .274, p < .001), and burnout (β = -.341, p < .001) were significant predictors of self-esteem, accounting for 45% of the variance (R² = .45, F(3,381) = 105.768, p < .001). The study concluded that, burnout is the strongest predictor of Self-Esteem among university students in Katsina state. The findings suggest that universities should prioritize interventions aimed at promoting students' self-esteem, managing academic anxiety, and preventing burnout. By understanding the complex relationships between these variables, stakeholders can develop targeted strategies to enhance students' self-esteem, academic performance, and overall well-being. The study's results have implications for educators, policymakers, and mental health professionals working with university students, highlighting the need for supportive learning environments and accessible mental health resources.